Evaluation of Immunity-related GTPase Family M Protein (IRGM) SNPs among Egyptian Lupus Patients: A Case-control Study - Ali, Ahmed Y.; Medhat, Basma M.; Ashour, Sara S.; Badr, Amul M.; Dorgham, Dalia; Ramadan, Hala; Behiry, Mervat E. (Current Rheumatology Reviews, 2023)
Objective: One of the potential factors that cause systemic lupus erythematosus (SLE) development is autophagy. Immunity-related GTPase family M protein (IRGM) has been shown to be linked to immune-mediated diseases. The aim of the current study was to assess the role of the IRGM-autophagy gene in SLE susceptibility in an Egyptian population and its relation to lupus nephritis. Methods: A case-control study was conducted in which a total of 200 subjects (100SLE and 100 healthy controls) were enrolled. Two single-nucleotide polymorphisms (SNPs) (rs10065172 and rs4958847) were genotyped. Genotypes and alleles analysis was conducted to compare between cases and controls, as well as a stratification analysis was conducted on the presence or absence of lupus nephritis. Results: Among selected SNPs of IRGM, no association was found between both SNPs and SLE susceptibility. For rs10065172, the major expressed genotype was CC (61% and 71%) (Adj OR= 2.9, 95%= 0.545-15.5), followed by TC (34% and 27%) (Adj OR= 1.985, 95% = 0.357-11.041) in cases and controls, respectively. For rs4958847, AA and AG were comparably expressed in case [(43% and 39%) (Adj OR= 1.073, 95% = 0.483-2.382)] and control [(41% and 43%) (Adj OR= 1.24, 95% = 0.557- 2.763)], respectively. Additionally, no relationship among both SNPs and gender, lupus nephritis, disease activity, or disease duration, was observed. Conclusion: IRGM SNPs (rs10065172 and rs4958847) expression was comparable among SLE patients and controls of the Egyptian cohort. Genotype and allele frequency of IRGM SNPs did not differ in lupus nephritis and non-lupus nephritis patients.
Keywords: Lupus